Olhar para o sol : concepção da análise fenomenológica hermenêutica - Medeiros, Geisa da Silva (2016)
The phenomenology, for dialogic educators, presents itself as essential tool in the critical evaluation and in the construction of different world views, for the teaching. Enables verification, study and explanation of phenomena in the classroom as well as those related to the prospects and directions of research in education. For your articulation, hermeneutics is applies, as understanding of reality, in the reflective/reflected and descriptive observation of phenomena with intentional consciousness and intended object. The hermeneutics was born in phenomenology, at the need to learn together, to understand reality, to grasp the intentions in its purest essence in the context of events. The hermeneutic phenomenology allows understanding and interpretation provides in the immersion of the observer in the world of observed, the approximation with the phenomenon and the restructuring of own worldview. The proposition of a qualitative research for teaching, with these concepcions, allows go to significant, emerging in the approximation in the phenomenon itself that, based on understanding and in the interpretation, search the meaning from the context in which the signifier is shown, with the inclusion of worldviews of the researcher himself, as an active subject of his research.